A Novel Humanized Anti-Interleukin-6 Antibody HZ0408b With Anti-Rheumatoid Arthritis Therapeutic Potential - Liu, Xiaolei; Li, Li; Wang, Qian; Jiang, Fengchao; Zhang, Pei; Guo, Fei; Liu, Hongjun; Huang, Jian (Frontiers in Immunology, 2022)
Interleukin-6 (IL-6), a pleiotropic cytokine that regulates immune responses and inflammatory reactions, plays a pivotal role in the development of rheumatoid arthritis (RA). Blockade of IL-6 signaling with the monoclonal antibody (mAb) represents an important advancement in RA treatment. Although two IL-6 receptor antibodies are already available in the clinic, there is no mAb specifically targeting the human IL-6 to block IL-6 signaling for RA treatment. In this study, we have developed a novel humanized anti-IL-6 mAb HZ-0408b with potent binding and neutralizing activity to human IL-6. We demonstrated that HZ-0408b has a high species specificity and low cross-reactivity. Moreover, HZ-0408b showed a more potent inhibitory effect on IL-6 signaling than Siltuximab, an FDA-approved anti-IL-6 chimeric mAb. HZ-0408b is comparable to Olokizumab, a humanized mAb against IL-6 that is already in phase III studies. We observed that HZ-0408b is well tolerated at doses that can achieve therapeutic serum levels in cynomolgus monkey. Most importantly, we proved that HZ-0408b treatment significantly ameliorated joint swelling after the onset of arthritis and dramatically reduced plasma C-reactive protein (CRP) levels in a monkey collagen-induced arthritis (CIA) model. Collectively, our findings using non-human primates indicate that humanized anti-IL-6 mAb HZ-0408b has excellent safety and efficacy profiles for RA therapy.